Fotografia e memória: o acervo Inah Emil Martensen nas décadas 1940-1950 - Macalossi, Ângela Marina (2012)
The research presented here concerns the matters ofanalysis and reading of pictures of a group of 26 artists whose artwork belong to the Municipal Photographic Library Ricardo Giovannini, at the city of Rio Grande, Rio Grande do Sul, Brazil. The pictures are part of the Inah Emil Martensen's Collection. The name of the collection is a tribute to one of the most distinguished persons of the cultural scene in Rio Grande at the 19th century. We will explain more about her relevance in this study. According to oral reports, we can infer that Inah Emil Martensen was a very important and activeperson in the artistic and cultural life of Rio Grande. Inah Emil Martensen acted as artist, influent woman, teacher, manager and event promoter. It was becauseof her relevance for the community that the Municipal Center of Culture was named after her, it is now called Municipal Center of Culture Inah Emil Martensen. In addition of a brief incursion into the universe of this emblematic figure in the history of Rio Grande, this research will examine more specifically the pictures of the 26 artists who were likely exhibiting in this municipality between 1940 and 1950. The photographs made this collection, once unknown,recognized and prominent among the community and the researchers. This study is about the subject of reading historical photographs, discussing documents as memory support and, consequently, as source of research